Perubahan Sifat Themal Tanah Pasiran Akibat Penambahan Limbah Organik - Muhjidin Mawardi (agriTECH, 2004)
Mass and heat transfer in a soil is much governed by its thermal properties. A laboratory experimentation has been done to investigate changes of thermal properties of sandy soil as influenced by organic waste mixed in the soil and the effect of the changes on soil moisture retention and evaporation. The samples of sandy soil is mixed with selected organic waste (i. e: sludge of leather industry, sludge of tapioca industry and composted green manure). The treated soil are then placed in PVC tubes, saturated with water and placed in greenhouse for measuring changes in soil properties during 50 days. Result of the experimentation shows that the organic waste mixed with sandy soil could significantly change its volumetric heat capacity and thermal regimes. The changes significantly affect the rate and amount of soil moisture loss through evaporation. During 50 days, the treated soil has lost 35 % of their soil moisture content. While the untreated (control) soil has lost 75 % of its soil moisture content.